18. REPORT ON A SERIES OF VAGINAL SPASMS TREATED AT THE CENTER FOR GENDER MEDICINE, HANOI ANDROLOGY AND FERTILITY HOSPITAL FROM 2022 TO 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: The understanding of physiology, pathogenesis vaginismus is still limited, so the treatment of vaginismus is challenging. Sex therapy is one of the therapy treatment vaginismus. Serial cases report of vaginismus treated with sex therapy. Subject and method: The serial cases with vaginismus presented including subjective reporting, clinical findings, diagnostics, and follow-up. Successful treatment determines when penetrative sex is possible. Female sexual function index (FSFI) was recorded before and after treatment. Results: We presented a 20 cases of female vaginismus treated with sex therapy, 19/20 patients were successfully. Female sexual function index improved from 7.1 points to 25.1 points 1 month after treatment. No adverse events or complications were recorded. Conclusions: Sex therapy seems to be a safe and successful remedy, low-cost one in terms of primary vaginismus treatment.
Keywords: Vaginismus, female sexual dysfunciton, sex therapy.